Climate governance: International experiences and implications for Vietnam - NGUYỄN THỊ THANH DUNG (Political Theory Journal, 2026)
Climate change is a global challenge that requires synchronized transformations in policy, institutions, and resources to respond effectively. This article analyzes the experiences of several countries in climate governance, from legal frameworks, Net-Zero strategies, and multi-level coordination mechanisms to financial instruments, thereby draws lessons and recommendations for Vietnam.